Ethanol content in different energy drinks available in Bangladesh - Hossain, MM; Jahan, I; Akter, S; Hasan, MM; Uddin, KR; Shawan, MMAK; Parvin, A; Hasan, MA; Ibrahim, M; Helali, MOH (Jahangirnagar University Journal of Biological Sciences, 2017)
Abstract not available Jahangirnagar University J. Biol. Sci. 5(2): 57-60, 2016 (December)